DISTRIBUTION OF CETACEANS IN SEAS SURROUNDING THE CHUKCHI PENINSULA (O Raspredelenii Kitoobraznyky v Moryakh, Omyvayushchikh Chukotskii Poluostrov) - Nikulin, I P (1969)
The whales were observed in Chukchi area by the author (1937-1941) and the seamen of the Aleut (1942-1943). It appears that Balaena mysticetus and Delphinapterus dorofeevi migrate north in April-May and south in December. Eschrichtius glaucus, Balaenoptera acutorostrata, B. physalus, Megaptera nodosa and Orcinus orca appear off the Chukchi Peninsula in June and remain there until the end of October. Trans. of Tikhookeanskii Nauchno-Issledovatelskii Institut Rybnogo Khozyaistva i Okeanografii. Izvestiya (USSR) v22 p255-257 1946, by M. Slessers.